2002
DOI: 10.1034/j.1600-051x.2002.290303.x
|View full text |Cite
|
Sign up to set email alerts
|

White blood cell count in generalized aggressive periodontitis after non‐surgical therapy

Abstract: The results indicate that a therapeutical intervention may have a systemic effect on the blood count in GAP patients. This effect seems to differ between smokers and non-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
(44 reference statements)
7
47
0
Order By: Relevance
“…It therefore appears that in vivo, P. gingivalis can survive in blood and host tissues [47,48]. Our results showing higher WBC counts in venous blood of patients with periodontitis concur with the results of other authors [15,17,18,49].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It therefore appears that in vivo, P. gingivalis can survive in blood and host tissues [47,48]. Our results showing higher WBC counts in venous blood of patients with periodontitis concur with the results of other authors [15,17,18,49].…”
Section: Discussionsupporting
confidence: 83%
“…The difference between smoking patients with periodontitis and smoking controls was not statistically significant. Christan et al [18] and Bokhari et al [51] found a significant reduction in WBC counts in venous blood after non-surgical therapy among non-smokers. Current knowledge suggests that smoking is associated with a less favorable response to periodontal therapy [50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that 90% of persons with refractory chronic periodontitis are smokers (Johnson & Slach, 2001). The healing following periodontal treatment is slower in smokers may be due to inhibition of growth and attachment of fibroblasts in the periodontal ligament and in slower reduction of white blood cells at diseased sites after therapy (Christan et al, 2002). Earlier studies showed no difference in prevalence of periodontal pathogens subgingivally (Preber et al, 1992), but more recent evidence suggests that smoking appears to promote a favorable habitat for pathogenic species in shallow pockets (Haffajee & Socransky, 2002).…”
Section: Risk Factorsmentioning
confidence: 99%
“…7,8 Aggressive periodontitis comprises a group of rare, often severe, rapidly progressive forms of periodontitis often characterized by an early age of clinical manifestation and a distinctive tendency for cases to aggregate in families. 1,9 Aggressive periodontitis describes three diseases formerly classified as early onset periodontitis. production of prostaglandin E2 (PGE2) and IL-1β in response to bacterial endotoxins.…”
Section: Introductionmentioning
confidence: 99%